POTENSI PEMANFAATAN KAWASAN CAGAR BUDAYA KALIURANG - Sholihah, Afifah; Prasodjo, Tjahjono (Universitas Negeri Gorontalo, 2024)
Regional Regulation of the Special Region of Yogyakarta Province No. 1 Year 2019 states that one of the development strategies for the southern slopes of Merapi is to develop the Kaliurang Cultural Heritage Area as an educational, cultural, and historical-based tourism area. In 2021, the Kaliurang area was designated as a regency-ranked cultural heritage area and then upgraded to a provincial rank In Kaliurang Cultural Heritage Area, there are several cultural heritage sites and buildings. This paper discusses the potential utilization of Kaliurang Cultural Heritage Area. The methods used are literature study and field observation. The discussion begins with an explanation of Kaliurang area as a cultural heritage area and then discusses Kaliurang Cultural Heritage Area as a tourism area based on education, culture, and history. The next discussion is the analysis of the potential utilization of cultural heritage areas based on the laws and regulations and the program recommendation, namely Cultural Heritage Exploration. The result of this study is that Kaliurang area has the potential to be utilized as a tourism area based on education, culture, and history. The utilization is in accordance with the existing laws and regulations related to the utilization of cultural heritage. The program recommendation, namely Cultural Heritage Exploration, is considered to be able to maintain the sustainability of the cultural heritage area, both physically and in terms of its importance, as well as to improve the welfare of the community.